2020
DOI: 10.1111/ans.16192
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Australian inguinal hernia repair rates: a 15‐year population study

Abstract: Background: An inguinal hernia is one of the most common surgical pathologies, and therefore the repair of an inguinal hernia is one of the most common general surgical procedures. The aim of this study was to assess the trend in inguinal hernia repair (IHR) rates in Australia between 2000/2001 and 2014/2015 using population data from public and private hospitals. Methods: ICD-10 data cubes from the Australian Institute of Health and Welfare were analysed to determine the number of inguinal hernia repairs perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Many surgeons now favour LIHRs for the repair of unilateral primary or recurrent and bilateral inguinal hernias. Consistently the percentage of LIHRs being performed in Australia is increasing 3,23 with a complimentary decline in OIHRs. Laparoscopic repairs now account for 44.0% of inguinal hernia repairs in Australia 2 .…”
Section: Discussionmentioning
confidence: 80%
“…Many surgeons now favour LIHRs for the repair of unilateral primary or recurrent and bilateral inguinal hernias. Consistently the percentage of LIHRs being performed in Australia is increasing 3,23 with a complimentary decline in OIHRs. Laparoscopic repairs now account for 44.0% of inguinal hernia repairs in Australia 2 .…”
Section: Discussionmentioning
confidence: 80%
“…The potential harm is that ultrasound findings may lead to unnecessary surgical repair and an increase in bilateral inguinal hernia repairs (IHRs) for contralateral occult inguinal hernias that would otherwise remain clinically insignificant, exposing patients to unnecessary risks of wound complications (haematoma and seroma), surgical site infections and long‐term chronic pain 3,4 . Previous work by one of our authors demonstrated an increase in bilateral IHRs in a similar patient population between 2000/2001 and 2014/2015, which was theorized as possibly being related to the anecdotal increase in the use of groin ultrasonography 11 …”
Section: Introductionmentioning
confidence: 83%
“…Inguinal hernia repair is a very common general surgical procedure, with a yearly incidence of 200 per 100,000 in Australia [1], while the lifetime risk of inguinal hernias is 27% in men and 3% in women [2]. The use of mesh is now conventional since 1989 when Lichtenstein published his success of the tension-free hernioplasty [3], but mesh has been used successfully since 1959 when Usher and colleagues demonstrated that Marlex polyethylene made into a monofilament mesh could be used for hernia repairs with low recurrence and infection risk [4].…”
Section: Introductionmentioning
confidence: 99%